Fluoride reduced the immune privileged function of mouse Sertoli cells via the regulation of Fas/FasL system. (February 2017) - Sun, Zilong; Nie, Qingli; Zhang, Lianjie; Niu, Ruiyan; Wang, Jundong; Wang, Shaolin
Abstract: Previous investigations have demonstrated the adverse impacts of fluoride on Sertoli cells (SCs), such as oxidative stress and apoptosis. SCs are the crucial cellular components that can create the immune privileged environment in testis. However, the effect of fluoride on SCs immune privilege is unknown. In this study, mouse SCs were exposed to sodium fluoride with varying concentrations of 10 −5, 10 −4, and 10 −3  mol/L to establish the model of fluoride-treated SCs (F-SCs) in vitro. After 48 h of incubation, F-SCs were transplanted underneath the kidney capsule of mice for 21 days, or cocultured with spleen lymphocytes for another 48 h. Immunohistochemical analysis of GATA4 in SCs grafts underneath kidney capsule presented less SCs distribution and obvious immune cell infiltration in F-SCs groups. In addition, the levels of FasL protein and mRNA in non-cocultured F-SCs decreased with the increase of fluoride concentration. When cocultured with F-SCs, lymphocytes presented significantly high cell viability and low apoptosis in F-SCs groups. Protein and mRNA expressions of FasL in cocultured F-SCs and Fas in lymphocytes were reduced, and the caspase 8 and caspase 3 mRNA levels were also decreased in fluoride groups in a dose-dependent manner. These findings indicated that fluoride influenced the testicular immune privilege through disturbing the Fas/FasL system. Graphical abstract: Highlights: Less Sertoli cells (SCs) and more lymphocyte infiltrations were observed in fluoride-treated SCs (F-SCs) grafts. F-SCs induced a significant high proliferation and low apoptosis of lymphocytes. The protein and mRNA expressions of FasL and Fas were reduced by F-SCs. Fluoride influenced immune privilege probably through disturbing the Fas/FasL system.